Sonography used in the infantile desmoid fibromatosis of postcricoid area: A case report. Issue 44 (November 2017) - Xia, Chunxia; Zhu, Qiang; Yue, Changli; Hu, Minxia; Li, Pingdong; Li, Zheng
Abstract: Rationale: Infantile desmoid fibromatosis of the postcricoid area is a rare disease and is characterized by a proliferation of fibrous tissue with non-metastasis, local infiltration, and a high rate of recurrence after surgical resection. Currently, ultrasound is scarcely used in the hypopharynx and larynx area. Patient concerns: A 4-year-old boy presented with hoarseness, deep voice and snoring for 2∼4 years without any surgical history. On sonography, the lesion was found in the postcricoid area, and the left larynx showed impaired mobility in real time observation. Complete excision with a negative margin in this pivotal anatomic area is impossible, and necessitates a long-time surveillance. Diagnoses: Infantile desmoid fibromatosis of the postcricoid area was diagnosed according to surgery and histopathology. Interventions: Local excision was carried out to relieve the upper airway narrowing. Outcomes: Relieved hoarseness and snoring were reported on the latest follow-up. A residual lesion was seen in the surgical bed and maintained a stable extent on ultrasound and MR imaging after a year. Lessons: Considering the non-radiation merit and diagnostic ability, ultrasonography is advocated as a valuable supplementary imaging method to CT, MR and laryngoscopy in the juvenile larynx and hypopharynx.